Probing the extragalactic fast transient sky at minute time-scales with DECam. Issue 4 (4th December 2019) - Andreoni, I; Cooke, J; Webb, S; Rest, A; Pritchard, T; Caleb, M; Chang, S-W; Farah, W; Lien, A; Möller, A; Ravasio, M E; Abbott, T M C; et al.
ABSTRACT: Searches for optical transients are usually performed with a cadence of days to weeks, optimized for supernova discovery. The optical fast transient sky is still largely unexplored, with only a few surveys to date having placed meaningful constraints on the detection of extragalactic transients evolving at sub-hour time-scales. Here, we present the results of deep searches for dim, minute-time-scale extragalactic fast transients using the Dark Energy Camera, a core facility of our all-wavelength and all-messenger Deeper, Wider, Faster programme. We used continuous 20 s exposures to systematically probe time-scales down to 1.17 min at magnitude limits g > 23 (AB), detecting hundreds of transient and variable sources. Nine candidates passed our strict criteria on duration and non-stellarity, all of which could be classified as flare stars based on deep multiband imaging. Searches for fast radio burst and gamma-ray counterparts during simultaneous multifacility observations yielded no counterparts to the optical transients. Also, no long-term variability was detected with pre-imaging and follow-up observations using the SkyMapper optical telescope. We place upper limits for minute-time-scale fast optical transient rates for a range of depths and time-scales. Finally, we demonstrate that optical g -band light-curve behaviour alone cannot discriminate between confirmed extragalactic fast transients such as prompt GRB flashes and Galactic stellar flares.